A Previously Undiagnosed Case of Alkaptonuria: A Case Report - Mohammed ALSBOU; Nesrin MWAFI (Archives of Rheumatology, 2013)
Alkaptonuria is a rare metabolic disorder in the phenylalanine and tyrosine catabolic pathway which is characterized by the excessive excretion of homogentisic acid in the urine, ochronosis, and debilitating arthritis of the spine and large joints. Although it is a very rare disease in most ethnic groups, it is more common in some countries, such Slovakia and the Dominican Republic. In this report, we report a 58-year-old Jordanian female case with advanced clinical features of alkaptonuria.